Pre-sprouted seedlings production methods through buds or mini-stems: Emergence and initial development of sugarcane cultivars - May, André; Ramos, Nilza Patrícia; De Souza Dos Santos, Michelli; Da Silva, Evandro Henrique Figueiredo Moura; Rossi, Paulo; Da Silva Viana, Ronaldo [UNESP] (UNESP - Universidade Estadual Paulista, 2018)
This study evaluates the emergence and initial development of sugarcane cultivars with different bud sizes, based on the system of pre-sprouted seedlings (PSS). Early sugarcane cultivars (RB966928, RB855156 and IACSP91-1099) were evaluated. These evaluations comprised three positions of the sugarcane stem (tip, middle and base) and four types of sugarcane propagules (mini-stem and 3 bud sizes with different diameters: 22 mm (1), 29 mm (2) and 35 mm (3)). Three trials were performed, each with a different cultivar. The experimental design for each cultivar was a randomized block in a 3×4 factorial scheme (stem position x propagule size (vegetative material)) with 4 replicates. Emergence was evaluated daily, and from these evaluations the emergence speed index (ESI) was calculated. Plant height, shoot dry mass and root dry mass were also assessed. Data were submitted to analysis of variance with interaction, and the Tukey test was applied. When simple variable transformations were not enough to meet the assumptions of normality and homoscedasticity, the non-parametric Friedman test was used. ESI indicated that the best type of propagule was the mini-stem, and for cultivars IACSP91-1099 and RB855156 the best performing position was the tip. The Friedman test indicated significance of the causes of variation related to propagule size and stem position for shoot dry mass in all evaluated cultivars. In addition, the test indicated significant variation of root dry mass for cultivars IAC91-1099 and RB966928 between propagule sizes and the stem positions. The height of cultivar IACSP91-1099 showed interaction between the different propagule sizes and stem positions. The greatest increase of height in sugarcane seedlings occurred for the mini-stem propagule and tip position. Cultivars RB855156 and RB966928 also showed interaction between the different propagule sizes and stem positions. Cultivar RB855156 showed the highest plant height with the mini-stem propagule at the tip position, however it did not differ statistically from the propagule with size 3 at the tip and middle positions. The mini-stem and the bud with size 3, removed from the tip of the stem, are the best alternatives for seedling production.
Keywords: Germination; PSS; Saccharum spp; Vegetative propagation